Pendidikan Karakter dalam Pembelajaran Sejarah - Yuhardi Yuhardi (Jurnal Kronologi, 2026)
This study aims to describe the implementation of character education in the history learning process and to identify the character values present in history learning materials. The research method used is a literature review. A literature review involves the analysis of data from various reference books and previous research relevant to the study to establish a theoretical foundation for the issue under investigation. The results of the study indicate that the implementation of character education in history learning begins with planning, implementation, and evaluation. Character values are derived from history materials rich in exemplary figures, interactive learning processes, the use of contextual learning models that encourage active student engagement, and evaluations in learning that focus not only on knowledge but also on students’ attitudes and behaviors as manifestations of the instillation of character values.